FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PEMBERIAN MP-ASI DINI PADA BAYI DI WILAYAH KERJA PUSKESMAS BASUKI RAHMAT KOTA BENGKULU - Suryani Suryani; S. Effendi; Nurmaya Pebrianti (Jurnal Sains Kesehatan, 2017)
The impact if  complementary foods was given early  is the infants will become more easily sick, ranging from cough, colds, fever, constipation, or diarrhea.               The purpose of this study was to study the factors associated with  early complementary feeding practices of  infants in working area of  Basuki Rahmat Public Health Center Bengkulu. This research used Cross Sectional design.                                     The population of this study was all mothers who had infants aged 7-12 months, amounting to 328 mothers. The sampling technique used Simple Random Sampling technique which amounted to 77 mothers. Data collection in this study used primary and secondary data with statistical test Chi-Square (χ2) through SPSS  program. The results of this study were from 77 mothers of  infants aged               7-12 months, 51 mothers (66.2%) had good knowledge, 51 mothers (66.2%) had             a pre-prosperous social economy, 44  mothers (57.1%) did not work, 59  mothers (76.6%) gave complementary  food age 6 months. There was no significant relationship between mother's knowledge, mother's work status, and social economy  with  early  complementary feeding  practices  in  working area of  Basuki  Rahmat  Public  Health Center Bengkulu. It was expected that Basuki Rahmad  Public Health Center to do counseling about exclusive breastfeeding and  complementary   feeding  practices  to pregnant women and mothers who have children under five in  working  area of  Basuki Rahmat  Public  Health Center Bengkulu. Keywords : complementary  food, employment status, knowledge, social economic